PERAN PEREMPUAN DALAM NAFKAH KELUARGA PERSPEKTIF HUKUM ISLAM - Aziz, Abdul (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
In the era of globalization and modernization, women earn a living, it has become a natural thing, as evidenced by the large number of working women. This is a change of role in society, especially in household life. Especially in economic problems, due to demands in fulfilling family needs where husbands can no longer meet the needs of their families because they are unable to earn more money or because of difficult circumstances in finding work, forced women to work to help their husbands to fulfill the economy in the family. The theory used in this study is the theory of gender equality. The research method used in this study is a qualitative method with an empirical juridical approach. The results of the study show that the role of women breadwinners can increase the economy of their families. Prosperity in the family goes well, because on average the breadwinner women are in prosperous families. So it can be seen that working women do not run all their household affairs well. breadwinner women can handle everything well without being neglected. The conclusion of this study is that Islam has regulated the rights and obligations of husband and wife so that the wheel of life in a household goes well in line with Islamic values. However, the times have changed the position of women with conditions that force women to play a dual role apart from being housewives, as well as being breadwinners in helping their husbands to achieve prosperity in married life.